Dosimetric analysis of standard tandem plus ring applicator in high dose rate (HDR) brachytherapy for cervical cancer: TLD measurement in phantom - Hamsir, Hazrul Haniff (Universiti Sains Malaysia, 2024)
Background: Standard Tandem Plus Ring applicator is one of the popular applicators utilised in intracavitary brachytherapy for cervical cancer. This is due to its geometry that easy to be employed and reproducible. However, a comprehensive understanding on the dosimetric behaviour of these applicator is required to improve the treatment efficacy and minimise organ at risks (OARs) toxicities. Purpose: This study aims to evaluate the dosimetric behaviour associated with the Standard Tandem Plus Ring applicator and to do a dose verification of the treatment plan for cervical cancer HDR brachytherapy. Methods: A Standard Tandem Plus Ring applicator was assembled in a heterogenous female pelvic phantom with thermoluminescence dosimeter (TLD-100) chips attached on the OARs. Computed Tomography (CT) images of the phantom was acquired, and treatment plan was created with 7 Gy dose prescribed to the tumour points. The OARs were ensured to receive dose within the tolerance which 6.5 Gy for bladder and 5.5 Gy for rectum. Eight dose points were noted in the treatment plan system (TPS), and they were compared with the dose measured by the TLD-100 chips during the phantom irradiation. Results: A pear-shaped dose distribution pattern was obtained, and dose received by 2 cm3 (D2cc) of the bladder and rectum were 1.767 Gy and 5.412 Gy respectively. Out of 8 dose points, 6 points have percentage deviation less than 20% while 2 points (E2 and E7) have deviation -23.133% and -24.222% between calculated and measured dose respectively. Conclusion: The percentage difference between DTPS and DTLD at the points of measurement have agreement within ±20%. Meanwhile, other points that have percentage deviation more than ±20% were due to individual limitation of the dosimeters itself.